One-step solid-oil-water emulsion for sustained bioactive ranibizumab release. (2nd December 2018) - Chua, Hui Yee; Lui, Yuan Siang; Bhuthalingam, Ramya; Agrawal, Rupesh; Wong, Tina; Preiser, Peter Rainer; Venkatraman, Subbu
ABSTRACT: Background : The advent of therapeutic proteins highlights the need for delivery systems that protect and extend the duration of its action. Ranibizumab-VEGF is one such drug used for treating wet AMD. This paper describes a facile method to sustain bioactive ranibizumab release from PLGA-based particles. Methods : Two emulsion techniques were explored namely: water-in-oil-in-water (WOW) and solid-in-oil-in-water (SOW) emulsion. The bioactivity of ranibizumab was evaluated by comparing its binding capability to VEGF, measured with ELISA to total protein measured by microBCA. Results : During the emulsion process, contact of ranibizumab with the water-oil interface is the main destabilizing factor and this can be prevented with the use of amphiphilic PVA and solid-state protein in WOW and SOW emulsion respectively. In vitro release of the ranibizumab-loaded particles indicated that a 15-day release could be achieved with SOW particles while the WOW particles generally suffered from a burst release. Released ranibizumab was capable of inhibiting endothelial cell growth indicating its retention of bioactivity. The suppression of burst release from the SOW particles was attributed to the relatively smooth surface morphology of the SOW microparticles. Conclusions : The use of SOW encapsulation in modulating ranibizumab release while maintaining their bioactivity has been highlighted.